The role of History textbooks in promoting historical thinking in South African classrooms (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article focuses on the analysis of three textbooks that are based on the Curriculum and Assessment Policy Statement (CAPS), a revised curriculum from the National Curriculum Statement which was implemented in 2008. The article uses one element of a historical thinking framework, the analysis of primary sources, to evaluate the textbooks. In the analysis of primary sources the three heuristics distilled by Wineburg (2001) such as sourcing, corroborating and contextualizing are used to evaluate the utilisation of the primary sources in the three textbooks. According to the findings of this article, the writing of the three textbooks is still framed in an outdated mode of textbooks’ writing in a dominant narrative style, influenced by Ranke’s scientific paradigm or realism. The three textbooks have many primary sources that are poorly contextualized and which inhibit the implementation of sourcing, corroborating and contextualizing heuristics. Although, some primary sources are contextualized, source-based questions are not reflecting most of the elements of sourcing, corroborating and contextualizing heuristics. Instead, they are mostly focused on the information on the source which is influenced by the authors’ conventional epistemological beliefs about school history as a compendium of facts. This poor contextualization of sources impacted negatively on the analysis of primary sources by learners as part and parcel of “doing history” in the classroom.
Keywords: Sourcing; Corroboration; Contextualisation; Realism; Epistemological belief; “Doing History”